2014
DOI: 10.4161/auto.28954
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal regulation of autophagy and dNTP pools in human cancer cells

Abstract: Ribonucleotide reductase (RNR) plays a critical role in catalyzing the biosynthesis and maintaining the intracellular concentration of 4 deoxyribonucleoside triphosphates (dNTPs). Unbalanced or deficient dNTP pools cause serious genotoxic consequences. Autophagy is the process by which cytoplasmic constituents are degraded in lysosomes to maintain cellular homeostasis and bioenergetics. However, the role of autophagy in regulating dNTP pools is not well understood. Herein, we reported that starvation- or rapam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 38 publications
3
36
1
Order By: Relevance
“…Following starvation, autophagy is induced to recycle cellular components and supply building blocks for metabolic pathways [62]. Indeed, autophagy-deficient cells accumulate DNA damage, presumably by excessive degradation of checkpoint proteins [9] or perhaps by deregulated dNTP metabolism [63]. From the disease relevance point of view, our present results support the view that autophagy can support tumour progression, at least in part by responding to oncogene-or genotoxic therapyinduced RS that stimulates autophagy flux.…”
Section: Discussionsupporting
confidence: 73%
“…Following starvation, autophagy is induced to recycle cellular components and supply building blocks for metabolic pathways [62]. Indeed, autophagy-deficient cells accumulate DNA damage, presumably by excessive degradation of checkpoint proteins [9] or perhaps by deregulated dNTP metabolism [63]. From the disease relevance point of view, our present results support the view that autophagy can support tumour progression, at least in part by responding to oncogene-or genotoxic therapyinduced RS that stimulates autophagy flux.…”
Section: Discussionsupporting
confidence: 73%
“…This suggests that ATRA induces CCR5 expression via mTOR-independent mechanisms and that mTOR regulation of HIV permissiveness in gut-homing CD4 + T cells likely occurs at postentry levels. Consistent with the evidence that mTOR regulates nucleotide biosynthesis essential for transcription (76,80,81), mTOR inhibitors may limit HIV reverse transcription by reducing the pool of nucleotides. Indeed, our single-round infection using VSV-Gpseudotyped HIV revealed restriction mechanisms acting during reverse transcription and prior to integration.…”
Section: On Hiv Replication In Ccr6mentioning
confidence: 54%
“…Despite upregulation of autophagy has widely been shown to promote DNA repair in cells treated with different DNA damaging agents [48][49][50], other studies revealed that excessive autophagy could induce genomic instability in cancer cells. For example, excessive autophagy has been shown to decrease the activity of ribonucleotide reductase and the production of deoxyribonucleoside triphosphates (dNTPs), leading to the induction of genomic instability in human cancer cells [51,52]. Furthermore, Huang et al demonstrated that targeting CTSS (cathepsin S) by small molecule inhibitors induced autophagy-dependent ROS production and the ROS-dependent DNA damage in HONE-1 cells [53].…”
Section: Discussionmentioning
confidence: 99%